Предмет: Математика, автор: karenchik20001

Упростить выражения.Сделайте пожалуйста)срочно надо

Приложения:

Ответы

Автор ответа: nnkalinka
0
( frac{1}{7}) ^{2-x}+49^{ frac{x}{2}}-7^{x+1}=7^{x-2}+7^{x}-7^{x+1}=7^{x-2}(1+7^{2}-7^{3})=7^{x-2}(1+49-343)=7^{x-2}(1+7^{2}-7^{3})=-293*7^{x-2}
 frac{1}{ sqrt{3} }* sqrt[4]{3}*( frac{1}{3})^{-3}=3^{- frac{1}{2} }*3^{ frac{1}{4} }*3^{3}=3^{-0,5+0,25+3}=3^{2,75}
 frac{a^{ frac{2}{3} }*a^{- frac{3}{2}}}{a^{ frac{3}{2} }*a^{- frac{1}{3}}}=frac{a^{ frac{2}{3} }*a^{ frac{1}{3}}}{a^{ frac{3}{2} }*a^{ frac{3}{2}}}= frac{a}{a^{3} }=a^{-2}
Похожие вопросы
Предмет: Математика, автор: Svanadze87